The correct completion of the dental record and its role in legal proceedings (Research, Society and Development, 2022)
The dental record is the essential document that must contain essential patient information that can be used as evidence of civil actions involving dental surgeons. Objective: to illuminate the importance of dental documents for the resolution of judicial issues. Methodology: This is a narrative literature review on the Google Scholar platform, on the website of the Constitution of the Federative Republic of Brazil and the Federal Council of Dentistry. Results:A way to prevent legal problems caused during dental treatment. Furthermore, it is necessary for the dental surgeon to correctly fill in the medical record, in order that this information can be used as judicial evidence. Conclusion: The growing number of civil lawsuits filed against dental surgeons is the result of the commercialization of dental work, and it is therefore important that these professionals prevent themselves, through the correct filling of dental documents, and are aware of their rights and duties.